Metabolic and genetic mechanisms of metabolic dysfunction-associated steatotic liver disease: an integrative perspective from molecular pathways to clinical challenges - Ma, Jingyuan; Ma, Yanna; Wan, Xing; Li, Junchen; Zhang, Yunshu; Liu, Jifeng; Gao, Yunhai (Frontiers in Endocrinology, 2025)
Metabolic dysfunction-associated steatotic liver disease (MASLD) is now the most common chronic liver condition worldwide, closely linked to obesity, insulin resistance, and metabolic syndrome. It spans a spectrum from simple steatosis to metabolic dysfunction-associated steatohepatitis (MASH), fibrosis, and hepatocellular carcinoma. This review examines the core metabolic disruptions—particularly in lipid, glucose, bile acid, amino acid, and iron metabolism—that drive MASLD pathogenesis. It also explores how genetic variants such as PNPLA3, TM6SF2, GCKR, HSD17B13, and MBOAT7 contribute to disease susceptibility and variability in clinical outcomes. The interaction between genetic background and metabolic stress is central to the heterogeneity seen in disease progression and treatment response. We further discuss persistent clinical challenges and summarize recent advances in drugs, natural compounds, and microbiota-based strategies. Finally, we highlight the promise of multi-omics approaches to better stratify patients and personalize management. A clearer understanding of the molecular and clinical complexity of MASLD will be key to developing more effective and individualized strategies for diagnosis and treatment.